LncRNA-miRNA-mRNA regulatory networks in skin aging and therapeutic potentials - Kim, Sungchul (Frontiers in Physiology, 2023)
Skin aging is a complex process influenced by intrinsic and extrinsic factors. Although dermatology offers advanced interventions, molecular mechanisms in skin aging remain limited. Competing endogenous RNAs (ceRNAs), a subset of coding or non-coding RNAs, regulate gene expression through miRNA competition. Several ceRNA networks investigated up to now offer insights into skin aging and wound healing. In skin aging, RP11-670E13.6-miR-663a-CDK4/CD6 delays senescence induced by UVB radiation. Meg3-miR-93-5p-epiregulin contributes to UVB-induced inflammatory skin damage. Predicted ceRNA networks reveal UVA-induced photoaging mechanisms. SPRR2C sequesters miRNAs in epidermal aging-associated alteration of calcium gradient. H19-miR-296-5p-IGF2 regulates dermal fibroblast senescence. PVT1-miR-551b-3p-AQP3 influences skin photoaging. And bioinformatics analyses identify critical genes and compounds for skin aging interventions. In skin wound healing, MALAT1-miR-124 aids wound healing by activating the Wnt/β-catenin pathway. Hair follicle MSC-derived H19 promotes wound healing by inhibiting pyroptosis. And the SAN-miR-143-3p-ADD3 network rejuvenates adipose-derived mesenchymal stem cells in wound healing. Thus, ceRNA networks provide valuable insights into the molecular underpinnings of skin aging and wound healing, offering potential therapeutic strategies for further investigation. This comprehensive review serves as a foundational platform for future research endeavors in these crucial areas of dermatology.